2007
DOI: 10.1016/j.clinbiomech.2007.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supraspinatus deficiency on humerus translation and glenohumeral contact force during abduction

Abstract: Background. Supraspinatus deficiency is the most frequent and important problem associated to rotator cuff pathologies. It reduces shoulder stability and can lead to osteoarthritis. The goal of this study was to develop a numerical model of the shoulder to analyse the biomechanical consequences of this pathology.Methods. A 3D finite element model of the shoulder was developed from a normal cadaver specimen. It included the scapula, the humerus and the major abduction muscles. Instead of the usual ball-socket a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 31 publications
0
87
1
4
Order By: Relevance
“…Indeed, significant fatigue progression was seen in the SSP and SUBS in the CG, and there was a trend towards fatigue progression in the ISP. Superior migration of the humeral head, in response to the increased and unbalanced contraction of the deltoid, is characteristic of MRCT [Terrier et al, 2007;Yamaguchi et al, 2000] which leads to the narrowing of the subacromial space and disruption of the glenohumeral fulcrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, significant fatigue progression was seen in the SSP and SUBS in the CG, and there was a trend towards fatigue progression in the ISP. Superior migration of the humeral head, in response to the increased and unbalanced contraction of the deltoid, is characteristic of MRCT [Terrier et al, 2007;Yamaguchi et al, 2000] which leads to the narrowing of the subacromial space and disruption of the glenohumeral fulcrum.…”
Section: Discussionmentioning
confidence: 99%
“…An MRCT often has significant impact on quality of life due to impaired shoulder strength and range of movement, and consequently reduced ability to perform essential daily activities. MRCT disrupts the glenohumeral fulcrum, leading to abnormal superior translation of the humeral head on the glenoid fossa during arm elevation as the destabilising force generated by the deltoid muscle is unopposed [Terrier et al, 2007;Yamaguchi et al, 2000]. The altered joint mechanics results in a disabling condition which can impact on functional capacity and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The second impingement between the glenoid component and superiorlateral border of the humerus was also expected. Using a numerical model preventing humeral head translation, Favre et al observed that an inferior translation of 5 mm of the humeral head within the resection plane limited the glenohumeral motion to 20 . 4 For the same malpositioning, our model predicted a similar impingement at 79 of humerothoracic angle, which corresponds roughly to 50 of glenohumeral angle.…”
Section: Discussionmentioning
confidence: 99%
“…A scapulo-humeral rhythm of 2:1 was assumed to replicate the motion of the scapula and the correct alignment of the muscle action relative to the arm weight. Detail of this numerical musculoskeletal model and its validation can be found in technical (Terrier et al, 2007;Terrier et al, 2008b) and clinical application papers (Terrier et al, 2008a;Terrier et al, 2009aTerrier et al, , 2009bTerrier et al, 2010).…”
Section: Methodsmentioning
confidence: 99%